Prevalence of Humility Character of High School Students in Semarang City and its Implications for Counseling Services at School - Naini, Rohmatus; Mulawarman, Mulawarman; Wibowo, Mungin Eddy (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2020)
The problem of low humility impacts bullying, arrogance, and anti-social behavior that is often found in schools. Humility is one of the character strengths, which is defined as the ability to accept suggestions from others, respect and respect others, not only think about yourself but also care about others. This study aims to determine the prevalence of the humility character of high school students in the city of Semarang. What conducted this survey research on 246 high school students aged 14-18 years. The instrument used to determine students' humility is the humility scale adapted from Elliot (2010) with 32 items with aspects including openness, self-forgetfulness, accurate self-assessment, and focus on others with a Likert scale type. The validity of the humility scale is 0.842, and the reliability is 0.901. Students with high humility are 182 students (74%), while 34 students (13.8%) and low 30% of students. The results showed that most students have high humility, and four aspects of humility have a significant relationship. The independent t-test results obtained sign 0.431 (p <0.05), meaning that there is no difference in the humility of male and female students. For further research, it is recommended to test the effectiveness of an intervention to increase humility with an individual or group counseling approach.